2001
DOI: 10.1038/sj.sc.3101197
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in the spinal cord injured: an epidemiological questionnaire investigation, including a normal population

Abstract: Study design: Epidemiological review. Objective: To evaluate sleep disturbances in the spinal cord injured. Setting: The Clinic for Para-and Tetraplegia, Hornbñk/Copenhagen, Copenhagen University hospital, Denmark. Methods: All patients admitted with traumatic SCI during the 20-year period 1968 ± 1987 were reviewed. The normal population consisted of 339, 222 men and 117 women. These groups were asked to ®ll in the self-administered Nordic Sleep Questionnaire (NSQ) containing 21 questions. Questions were added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
81
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 53 publications
11
81
1
Order By: Relevance
“…Thus, the absence of night time melatonin secretion may explain part of the excessive daytime sleepiness and disturbed sleep observed in patients with cervical SCI. [1][2][3] Furthermore, the increased latency to REM sleep in subjects with cervical SCI suggests that the absence of night time melatonin may partially underlie the previously observed reduction in REM sleep propensity. 2 Melatonin has been proposed to facilitate sleep by inhibiting the circadian drive for waking that emanates from the SCN, [11][12][13] by binding to the high-affinity melatonin receptors in the human SCN 14 (for a review, see Scheer et al 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the absence of night time melatonin secretion may explain part of the excessive daytime sleepiness and disturbed sleep observed in patients with cervical SCI. [1][2][3] Furthermore, the increased latency to REM sleep in subjects with cervical SCI suggests that the absence of night time melatonin may partially underlie the previously observed reduction in REM sleep propensity. 2 Melatonin has been proposed to facilitate sleep by inhibiting the circadian drive for waking that emanates from the SCN, [11][12][13] by binding to the high-affinity melatonin receptors in the human SCN 14 (for a review, see Scheer et al 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] We previously found that patients with complete lesions of their cervical spinal cords have an absence of the normal endogenous melatonin secretion at night. This demonstrates that the neural pathway for the endogenous production of melatonin passes through the cervical spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…They take more sleeping pills, and their snores are prolonged and more frequent than those of healthy persons. 1,2 These sleep disturbances may be caused by spastic muscle contractions, pain, sensory disturbances, or incontinence. Impairment of the sleep-wake cycle, a possible consequence of a cervical SCL, may also contribute to these disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Biering-So¨rensen, 16 differences in sleep quality between patients with an SCI and individuals from the general population were assessed with the Nordic Sleep Questionnaire. They found that patients with SCI had poorer sleep quality, for example, reported more difficulties falling asleep, awakened more often at night, slept subjectively less well, were more often prescribed sleeping pills, slept more hours, took more and longer naps, and snored more.…”
Section: Introductionmentioning
confidence: 99%